Establishment of the International Criminal Court and the Role of USA: A Legal Appraisal (Northern University Journal of Law, 2014)
In order to end global impunity of perpetration of heinous crimes against humanity and gross violation of human rights and to bring individual perpetrators to justice, international community felt the need for a permanent international criminal court.2 As the armed conflicts and serious violations of human rights and humanitarian law continue to victimize millions of people throughout the world, the reasons for an international criminal court became compelling.3 In many conflicts around the world, armies or rebel groups attack ordinary people and commit terrible human rights abuses against them. Often, these crimes are not punished by the national courts. Here the ICC is complementary to national criminal jurisdictions.4 The court only acts in cases where states are unwilling or unable to do so.5 The jurisdiction of the Court is not retrospective and binds only those States that ratify it.6 Unlike the International Court of Justice in The Hague, whose jurisdiction is restricted to states, the ICC has individualized criminal responsibility. However, the role of USA regarding the establishment and continuation of ICC has caused the organization fall in a trouble. The better cooperation of USA and other states could make the organization more active and effective as to its activities. The view of this paper is to analyze the role of USA towards the establishment, continuation and function of the International Criminal Court. DOI: http://dx.doi.org/10.3329/nujl.v1i0.18525 Northern University Journal of Law Vol.1 2010: 51-69